Agricultural Development under a Changing Climate : Opportunities and Challenges for Adaptation - Padgham, Jon (World Bank, Washington, DC, 2017)
Climate change presents a profound challenge to food security and development. Negative impacts from climate change are likely to be greatest in regions that are currently food insecure and may even be significant in those regions that have made large gains in reducing food insecurity over the past half-century. Adaptation in the agricultural sector is being given a high priority within this effort because of the inherent sensitivity of food production to climate and the strong inter-linkages that exist between climate, agriculture, and economic growth and development. The purpose of this report is to review the major effects of climate change on the agricultural sector; to examine the causes of vulnerability; and to suggest a range of potential options and investment opportunities for supporting adaptation efforts and, more generally, for building adaptive capacity. This report primarily focuses on appropriate strategies for adapting to climate change impacts that are projected to occur over the next one to two decades, although several issues covered in this report are important for long-term adaptation needs as well. This report also describes opportunities for linking adaptation and mitigation, and it discusses the importance of mainstreaming adaptation into development.